2017
DOI: 10.1155/2017/6875968
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Evaluating the Effects of Diosmin in the Treatment of Radicular Pain

Abstract: Diosmin has been widely used to treat patients with vascular pain for its potent anti-inflammatory and analgesic effects. To evaluate the therapeutic effects of Diosmin in the treatment of radicular pain, we conducted an investigator-initiated, randomized, active-controlled noninferiority trial between January 1, 2009, and December 1, 2010. Diosmin (50 mg/kg/day) was orally administered to treat the radicular pain in 150 patients for one month. Another 150 patients with the same symptom were given 20% 250 ml m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 38 publications
(30 reference statements)
1
8
0
Order By: Relevance
“… 339 , 340 Diosmin is a citrus flavonoid (diosmetin 7‐O‐rutinoside) non‐prescription dietary supplement that has been trialed for the treatment of LBP. 294 Diosmin is reported to reduce chronic constriction injury‐induced neuropathic pain in mice 292 and provides central and peripheral anti‐hyperalgesic effects in a neuropathic pain model in rats. 293 The related flavonoid hesperidin has anti‐hyperalgesic properties in a neuropathic pain model in rats.…”
Section: Anti‐inflammatory Phytochemicals Displaying Ivd ...mentioning
confidence: 99%
See 1 more Smart Citation
“… 339 , 340 Diosmin is a citrus flavonoid (diosmetin 7‐O‐rutinoside) non‐prescription dietary supplement that has been trialed for the treatment of LBP. 294 Diosmin is reported to reduce chronic constriction injury‐induced neuropathic pain in mice 292 and provides central and peripheral anti‐hyperalgesic effects in a neuropathic pain model in rats. 293 The related flavonoid hesperidin has anti‐hyperalgesic properties in a neuropathic pain model in rats.…”
Section: Anti‐inflammatory Phytochemicals Displaying Ivd ...mentioning
confidence: 99%
“…Lycorine reduces proinflammatory cytokine production and protects cartilage from degradation by MMPs in a mouse model of OA 339,340 . Diosmin is a citrus flavonoid (diosmetin 7‐O‐rutinoside) non‐prescription dietary supplement that has been trialed for the treatment of LBP 294 . Diosmin is reported to reduce chronic constriction injury‐induced neuropathic pain in mice 292 and provides central and peripheral anti‐hyperalgesic effects in a neuropathic pain model in rats 293 .…”
Section: Anti‐inflammatory Phytochemicals Displaying Ivd Cell Protect...mentioning
confidence: 99%
“…intramuscular (three trials) 22,23,25 or by intravenous injection (four trials). 26,27,30,31 The most common corticosteroid drugs used were dexamethasone (six trials [23][24][25][26]30,31 ) methylprednisolone (two trials, 22,27 ) and prednisolone (one trial 29 ) Corticosteroid dosages standardized for dexamethasone potency equivalence ranged from 8 mg to 156 mg. The rate of completers was generally high (76.2%-100%), except for one study that showed a compliance rate between 55.2% and 69.0% (Table 1).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Seven entries from four studies 22,[29][30][31] were pooled in the meta-analysis for pain intensity, showing a significant superior reduction of pain following corticosteroid treatment (SMD = −0.42, 95% CI −0.76 to −0.08, weak effect, very-low certainty). When subgrouping by the duration of follow-up, a significant reduction of pain was only seen at immediate (SMD = −0.87, 95% CI −1.46 to −0.27, large effect) and short-term follow-up (SMD = −0.97, 95% CI −1.24 to −0.73, large effect).…”
Section: Improvement Of Proms and Slrmentioning
confidence: 99%
See 1 more Smart Citation